(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Hysterectomy is one of the most frequently performed major surgical procedure. Majority of the hysterectomies are still done by the means of abdominal route. Despite its common performance, there are no grade A recommendations or guidelines regarding closure of vaginal vault. Surgical technique of hysterectomy may include either closed or open vaginal vault. This study aimed to compare these two techniques in terms of duration of hospital stay, febrile morbidity, vault hematoma, vaginal bleeding, relaparatomy to provide further guidance for surgical decisions. Method: This is a retrospective study done at Patan Hospital involving patients with total abdominal hysterectomy from January 2018 to December 2020. Data were collected from medical record. Statistical analysis was done using Statistical Packages for Social Sciences (SPSS-20). The independents sample t test was used. A p value of <0.05 were considered statistically significant Result: Of the 280 surgeries, 205 (73.2%) had vaginal vault closed whereas 75 (26.8%) were open. Mean length of hospital stay was 7.93 days with standard deviation of 3.108. Closed and open vaginal vault techniques did not differ in terms of length of hospital stay (7.83 vs. 8.19 days; p=0.40), febrile morbidity (54.6% vs. 52%; p= 0.695). Pelvic hematoma with vaginal spotting was seen in two (0.71%) cases of closed vaginal vault. Conclusion: Both techniques of hysterectomy gave similar outcomes regarding length of hospital stay, showed no significant difference regarding postoperative complications. Our study failed to show inferiority in favor of either of the surgical techniques.